PERICARDIAL NEO-AORTA FOR RESOLUTION OF A VASCULAR CATASTROPHY. INNOVATIVE SOLUTION FOR AORTIC PROSTHETIC INFECTION. - Afonso, Ana (2019)
Introduction and Purpose: Aortic prosthetic graft infection is a rare but potentially fatal complication. Treatment require the complete excision of the prosthetic material, debridement of the surrounding tissues, broad-spectrum antibiotics, and limb revascularization which can be done through in situ reconstruction or by extra-anatomic solutions. The authors present a case of an in situ reconstruction with bovine pericardium graft. Methods and Results: We report a case of a patient, previously submitted to a aortic-bifemoral bypass with Dacron prosthesis complicated of infection six years after and treated with complete excision and in-situ reconstruction with bifurcated Dacron silvergrat and antibiotics for life. One year after the patient develop bilateral pulsatile groin mass with inflammatory signs and fever. The computed tomography showed signs of prosthetic infection, aposition of D3 duodenal portion with the underlying prosthesis. The patient is submitted a total graft excision, fistulectomy with duodenojejunostomy and an in situ aortic reconstruction with a Y graft tailored from a self-made tube graft from bovine pericardium and endarterectomized superficial femoral arteries. The patient underwent a 45 days antibiotic regimen and it was discharged with an overall good condition.   Discussion and Conclusion: Patients with infectious aortic disease present in a frail state and with high risk of mortality and morbidity. Because of their off-the-shelf availability, handling properties, and freedom from reinfection and durability, self-made bovine pericardial grafts are an useful option in urgent reconstruction of vascular infections.